START DEVELOPING THE SKILLS OF APPROPRIATE USE OF ANTONYMS IN THE CLASSROOMS (Scientific journal of the Fergana State University, 2024)
This article describes the concept of words with opposite meanings, their content, and development. Methods for developing students' skills in using words with opposite meanings in everyday speech situations have been developed. Methods for developing skills in using textbooks when teaching antonyms to elementary school students are highlighted. Antonyms in the native language and in literacy lessons in elementary school are indicated. The functions of z are also specified, as well as information on their correct use. There are many opportunities in our language to use units with opposite meanings. Their correct and appropriate use is one of the most important factors in enhancing speech richness. Additionally, the article reveals the significance of words with opposite meanings through various examples.